Building agency through technology-aided dialogic teaching. (September 2020) - Omland, Maren; Rødnes, Kari Anne
Abstract: Rooted in the sociocultural tradition, this article examines how one teacher helps her eighth-grade students build agency through dialogic teaching supported by technology. Students' agency is essential for their participation in dialogues and thereby their learning processes, making it vitally important to understand how teachers can support and enhance their students' development of agency. This study is a part of a design-based study introducing a dialogic approach to teaching and learning with the aid of technology. The empirical data comprise video-observations from classrooms and interviews with the teacher and students that we analysed using interaction analysis. The results show how teachers may practice specific dialogic moves, such as asking open questions and acknowledging students' contributions. Further, we show how technology may be used to position student contributions as a central focus point in the dialogue. This paper explains why these strategies work by pointing out interrelations between agency, positioning and dialogue. We emphasize both individual and social aspects of agency and show how they are intertwined.